Volatile metabolites from new cultivars of catnip and oregano as potential antibacterial and insect repellent agents - Patel, Harna K.; Gomes, Erik Nunes; Wu, Qingli; Patel, Nrupali; Kobayashi, Donald Y.; Wang, Changlu; Simon, James E. (Frontiers in Plant Science, 2023)
Plant based natural products have been widely used as antibacterial and insect repellent agents globally. Because of growing resistance in bacterial plant pathogens and urban pests to current methods of control, combined with the long- and short-term negative impact of certain chemical controls in humans, non-target organisms, and the environment, finding alternative methods is necessary to prevent and/or mitigate losses caused by these pathogens and pests. The antibacterial and insect repellent activities of essential oils of novel cultivars of catnip (Nepeta cataria L. cv. CR9) and oregano (Origanum vulgare L. cv. Pierre) rich in the terpenes nepetalactone and carvacrol, respectively, were evaluated using the agar well diffusion assay and petri dish repellency assay. The essential oils exhibit moderate to high antibacterial activity against three plant pathogens, Pseudomonas cichorii Swingle (Stapp), Pseudomonas syringae van Hall and Xanthomonas perforans Jones et al. of economic interest and the individual essential oils, their mixtures and carvacrol possess strong insect repellent activity against the common bed bug (Cimex lectularius L.), an urban pest of major significance to public health. In this study, the essential oils of catnip and oregano were determined to be suitable candidates for further evaluation and development as antibacterial agents and plant-based insect repellents with applications in agriculture and urban pest management.